The attitudes and perceptions of adolescent track and field athletes toward PED use - Judge, L. W.; Bellar, D.; Petersen, J.; Lutz, R.; Gilreath, E.; Simon, L.; Judge, M. (Performance Enhancement & Health, 2012)
The practice of enhancing athletic performance through the use of extraneous artificial means is as old as competitive sport itself. Very little research assessing the attitudes of adolescent strength/power athletes concerning ergogenic aids exists. As national anti-doping organizations (NADOs) and even state and local athletic associations adopt preventative measures to complement detection-based deterrence methods, understanding adolescent athlete attitudes towards drugs in sport will take on a new importance. This study was conducted to measure athlete attitudes in the sport of track and field (specifically throwers) toward performance enhancing drug (PED) use and drug testing using the theory of planned behavior (TPB) framework. The sample was comprised of 46 males (mean age = 15.9, SD = 2.2 years) and 52 females (mean age = 15.8, SD = 1.9 years). A 4-step hierarchical regression was employed to determine how study variables predicted intent to use PEDs. Gender did not predict significant variance in intent (R2 = .04; p = .06), but the theory of planned behavior constructs (R2 change = .46; p < .001), attitude strength and moral conviction (R2 change = .06; p < .05), and the interaction of attitude with moral conviction (R2 change = .04; p < .01) did predict significant variance in intent for PED use. In the final model, significant predictors of intent included attitude, injunctive norms, attitude strength (centrality), moral conviction, and the attitude by moral conviction interaction. The conclusions of the present study show that attitude strength and moral conviction are important considerations in understanding PED use.